Time cost associated with sports participation for athletes with high support needs: a time-motion analysis of tasks required for para swimming. Issue 4 (5th October 2022) - Dutia, Iain; Curran, Declan; Donohoe, Adam; Beckman, Emma; Tweedy, Sean Michael
Abstract : Objectives: People with cerebral palsy and high support needs (CP&HSN) are profoundly inactive but also under-represented in studies evaluating physical activity interventions. Reasons for their exclusion have not been evaluated. We hypothesised that CP&HSN would be associated with high time costs of preparatory activities (eg, getting dressed/undressed), possibly contributing to low participation and under-representation. Accordingly, this pilot study aimed to: (1) evaluate whether the time required for preparatory activities was extremely different (≥3 SD) between swimmers with and without CP&HSN; and (2) provide a qualitative indication of the preparatory tasks undertaken by swimmers with CP&HSN. Methods: Each of three experienced (5 years) para swimmers with CP&HSN and 20 non-disabled swimmers were timed entering and then exiting the pool on three occasions. Mean entry and exit time for each para swimmer was compared with the group mean for non-disabled swimmers, and differences of greater than 3.0 SD were considered extreme. A qualitative description of the tasks completed by the para swimmers was recorded. Results: The differences in time costs between para and non-disabled swimmers met the criterion of extreme. Pool entry times for para swimmers were 8–13 times greater (Effect size = 4.1–8.7). Pool exit times were 6–10 times greater (ES=7.0–9.5). 90% of tasks completed by para swimmers required personal assistance or wheeled mobility. Conclusions: This pilot study suggests that, compared with non-disabled swimmers, time costs for preparation to commence or depart training are extremely high for swimmers with CP&HSN. Further research is required to evaluate the veracity of these findings.